2017
DOI: 10.1016/j.alit.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in the diagnosis and classification of nonsteroidal anti-inflammatory drug hypersensitivity reactions in children

Abstract: This study suggests the presence of different phenotypes which do not fit into the current classifications in children with NSAID hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 34 publications
0
52
0
3
Order By: Relevance
“…Zambonino et al reported that mainly food allergy, but also inhalant allergen sensitization, was significantly more frequent in CI children and adolescents compared to SRs and healthy controls, and sensitization to, particularly, house dust mites, Olea europaea, and Alternaria was the most frequently associated inhalant allergens . Nevertheless, these findings were not confirmed in other studies . The clinical manifestations occurring during the index reaction may also be predictive of the result of a provocation test.…”
Section: Risk Factors For Nsaid‐h In Childhoodmentioning
confidence: 94%
See 4 more Smart Citations
“…Zambonino et al reported that mainly food allergy, but also inhalant allergen sensitization, was significantly more frequent in CI children and adolescents compared to SRs and healthy controls, and sensitization to, particularly, house dust mites, Olea europaea, and Alternaria was the most frequently associated inhalant allergens . Nevertheless, these findings were not confirmed in other studies . The clinical manifestations occurring during the index reaction may also be predictive of the result of a provocation test.…”
Section: Risk Factors For Nsaid‐h In Childhoodmentioning
confidence: 94%
“…Cutaneous symptoms such as urticaria and angioedema are the most frequent reactions appearing during NSAID‐induced hypersensitivity reactions in children . In adults, the most frequent clinical manifestation is CI type urticaria and/or angioedema and to a lesser extent respiratory involvement, whereas in children, there are contradictory results . In one of the largest published series, there were slightly more cross‐intolerant patients than selective responders, but this was not the case in smaller studies .…”
Section: Epidemiology and Clinical Manifestations In Different Phenotmentioning
confidence: 99%
See 3 more Smart Citations